Radiological hazard assessment of natural radionuclides and heavy metal pollution in deep mud samples of Van Lake, Turkey - Kayakoku, Halime; Dogru, Mahmut (Springer, 2020)
In this study, the natural radioactivity levels were determined for the deep mud samples taken from Van Lake. Ra-226, Th-232 and K-40 natural radionuclides concentration analysis were performed using high-purity germanium detector and relevant radiological hazard parameters were also appraised. Furthermore, the concentrations of heavy metals were measured using ICP-OES device. While the average Ra-226, Th-232 activity concentrations were higher than the world average values, the average K-40 concentration was lower than the world average. The average metal concentrations were found to be higher than the highest effective levels reported in national and international quality guidelines (except Cr and Zn).
Keywords: Natural radioactivity; Gamma-ray spectrometry; Dose rates; Heavy metal; Deep mud; Van Lake